High-performance in-situ thermal cross-linking three-dimensional aqueous binder and method for preparing silicon-based negative electrode sheet using the binder

By using high-performance in-situ thermally crosslinked three-dimensional water-based adhesive in lithium batteries, the three-dimensional mesh structure is formed, which solves the problem of electrode structure integrity caused by volume expansion of silicon-based materials in lithium batteries, and improves the cycle stability of the battery performance and rate performance.

CN115548340BActive Publication Date: 2025-01-17XIAMEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211187256.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2025-01-17
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

The volume expansion of silicon-based materials in lithium batteries during charging and discharging leads to damage to the integrity of the electrode structure and hindering the transmission of electrons and ions, resulting in cyclic stability and capacity attenuation problems.

Method used

Using high-performance in-situ heat crosslinked three-dimensional water-based binder, the in-situ condensation reaction of alkalized polyethylene maleic acid and natural hydroxyl-rich binder forms a three-dimensional network structure, and bake it with appropriate temperature to enhance the binder The viscosity and adhesion of the active material and the conductive agent form a good contact network.

Benefits of technology

It effectively improves the rate performance, cycle life and cycle stability of lithium batteries, alleviates the problem of silicon matrix volume expansion, and significantly improves battery capacity attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115548340B_ABST
    Figure CN115548340B_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance in-situ thermal cross-linking three-dimensional aqueous binder and a method for preparing a silicon-based negative electrode sheet using the binder, and relates to the technical field of lithium battery preparation. The binder includes a P(E-alt-MA)-0.25Li2 aqueous binder and a natural hydroxyl-rich binder mixed with each other, wherein the weight ratio of the P(E-alt-MA)-0.25Li2 aqueous binder to the natural hydroxyl-rich binder is 1:1. The present invention starts with the binder used in the battery manufacturing process, uses alkalized polyethylene maleic acid and a natural hydroxyl-rich binder to prepare a composite binder, and the two binders are cross-linked by an in-situ condensation reaction to form a three-dimensional network structure, and the vacuum baking temperature of the pole piece is changed, the integrity of the electrode structure is maintained during the pole piece manufacturing process, and the contact between the active material and the conductive agent is better, forming an excellent conductive network, thereby effectively improving the rate performance, cycle life and cycle stability of the battery, and improving the problem of lithium battery capacity decay.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery preparation, and in particular to a high-performance in-situ thermally cross-linked three-dimensional aqueous binder and a method for preparing a silicon-based negative electrode sheet using the binder. Background Art

[0002] Lithium batteries are a type of battery that uses lithium metal or lithium alloy as positive / negative electrode materials and non-aqueous electrolyte solutions. They can be roughly divided into two categories: lithium metal batteries and lithium-ion batteries. Currently, lithium-ion batteries are expanding from traditional portable electronic products to large-scale energy storage fields such as electric vehicles and power grids.

[0003] The negative electrode of lithium ions can be divided into carbon-based negative electrodes and non-carbon-based negative electrodes. Carbon-based negative electrode materials can be specifically divided into negative electrode materials such as graphite, hard carbon, soft carbon and graphene. Non-carbon-based negative electrode materials include titanium-based materials, silicon-based materials, tin-based materials and nitrides.

[0004] In the current research of lithium-ion batteries, most of the work focuses on positive and negative electrode materials, electrolytes, or the design of battery structures. Among them, silicon-based materials are the focus of current research. Due to its high theoretical specific capacity, low lithium insertion potential and abundant reserves, silicon is considered to be a potential negative electrode material for the next generation of high energy density lithium-ion batteries.

[0005] For example, a Chinese patent with patent number CN110380029B discloses a silicon-based negative electrode material for lithium batteries, which includes a silicon source material and a carbon source material, wherein the silicon source material and the carbon source material are compounded into a tightly packed body with a pomegranate-shaped structure, and the carbon source encapsulates the silicon source, and the silicon source is tightly distributed in the gaps of the carbon source. This material solves the problem of volume expansion of nano-silicon-based materials to a certain extent.

[0006] Another example is a Chinese patent with publication number CN111129479B, which discloses a stable lithium battery silicon-based negative electrode material and a preparation method thereof, comprising silicon oxide nanosheets, graphene oxide, epoxy resin, curing agent and lithium salt; wherein the epoxy resin is an epoxy resin containing flexible polyurethane, and the curing agent is a fatty amine compound containing a flexible polyether segment. The product obtained by this method can maintain good stability during long-term charge and discharge cycles.

[0007] Compared with Si, carbon-coated SiOx has attracted extensive commercial attention due to its smaller volume expansion and longer cycle life. However, the volume of SiOx will also change during the charging and discharging process, which will affect the integrity of the electrode structure and seriously hinder the effective transmission of electrons and ions. On the other hand, the pulverization and rupture of the electrode will lead to the leakage of active particles, which will cause further decomposition of the electrolyte and fail to form a stable SEI film, ultimately resulting in poor cycle stability of the negative electrode material. Therefore, the capacity attenuation and cycle stability of silicon-based materials are still one of the most important issues in the current commercial application of silicon-based materials. It is a problem that is difficult to alleviate in the preparation of lithium batteries. Summary of the invention

[0008] The present invention aims at solving the above-mentioned technical problems, overcomes the shortcomings of the prior art, and provides a high-performance in-situ thermally cross-linked three-dimensional aqueous binder and a method for preparing a silicon-based negative electrode sheet using the binder.

[0009] Technical effect: The present invention starts with the binder used in the battery manufacturing process, uses alkalized polyethylene maleic acid and natural hydroxyl-rich binder to make a composite binder, and makes the two binders undergo an in-situ condensation reaction for cross-linking to form a three-dimensional network structure, and changes the vacuum baking temperature of the electrode piece. During the electrode piece preparation process, the integrity of the electrode structure is maintained, and the active material and the conductive agent are in better contact to form an excellent conductive network, thereby effectively improving the battery's rate performance, cycle life and cycle stability, and improving the problem of lithium battery capacity attenuation.

[0010] The technical solution further defined in the present invention is: a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, comprising a P(E-alt-MA)-0.25Li2 aqueous binder and a natural hydroxyl-rich binder which are mixed with each other to form a composite binder, wherein the weight ratio of the P(E-alt-MA)-0.25Li2 aqueous binder to the natural hydroxyl-rich binder is 1:1.

[0011] Furthermore, the P(E-alt-MA)-0.25Li2 aqueous binder is alkalized polyethylene maleic acid, including polyethylene maleic anhydride, ultrapure water and lithium hydroxide mixed with each other, wherein the weight proportion of polyethylene maleic anhydride accounts for 5% of the total weight of the P(E-alt-MA)-0.25Li2 aqueous binder.

[0012] The high-performance in-situ thermally cross-linked three-dimensional aqueous binder and the method for preparing a silicon-based negative electrode sheet using the binder as mentioned above, the natural hydroxyl-rich binder is an Alg binder or a chitosan binder or a carboxymethyl cellulose binder, and the concentration of the natural hydroxyl-rich binder is 5%, and the baking temperature is 150°C when the composite binder is used to prepare the electrode sheet.

[0013] The present invention also provides a method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, comprising the following substances in a content ratio:

[0014] Carbon-coated silicon 94%

[0015] Conductive carbon black 3%

[0016] Single-walled carbon nanotubes 1%

[0017] 5% concentration of P(E-alt-MA)-0.25Li2 aqueous binder 1%

[0018] 1% natural hydroxyl-rich binder at a concentration of 5%.

[0019] In the above-mentioned method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, the natural hydroxyl-rich binder is prepared from a hydroxyl-rich compound.

[0020] The above-mentioned method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder comprises the following steps:

[0021] S1, preparation of 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder, take 2.375 parts of polyethylene maleic anhydride and 47.425 parts of ultrapure water, heat and stir to mix in a water bath, the stirring temperature is 60°C; then take 0.2 parts of lithium hydroxide and add it to the prepared polyethylene maleic anhydride solution, let it react for 4 to 6 hours until the solution is clear, and obtain a 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder;

[0022] S2, preparation of a 5% concentration natural hydroxyl-rich binder, taking 5 parts of a hydroxyl-rich compound, adding it to 95 parts of ultrapure water, heating and stirring in a water bath at a stirring temperature of 60° C., and preparing a natural hydroxyl-rich binder;

[0023] S3, preparation of negative electrode sheet, take corresponding contents of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and natural hydroxyl-rich binder, mix them in the ratio of 94:3:1:1:1, stir for 10 minutes, and obtain a uniformly dispersed slurry; take copper foil of specified size, evenly apply the prepared slurry on the surface of the copper foil, and dry it at 80°C for 10 hours, and then vacuum dry it at 150°C for 8 hours, and finally cut it into specified size to obtain a finished negative electrode sheet.

[0024] In the above-mentioned method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, the hydroxyl-rich compound is sodium alginate powder or chitosan or sodium carboxymethyl cellulose powder.

[0025] The beneficial effects of the present invention are:

[0026] (1) In the present invention, two binders that can cross-link with each other are used. Usually, when preparing the negative electrode sheet, only one binder needs to be added. In a few preparation methods that add two binders, no chemical reaction occurs between the two binders. However, when the polyethylene maleic acid and natural hydroxyl-rich binder used in the present invention are baked at an appropriate temperature, the two binders can undergo an in-situ condensation reaction to cross-link and form a composite binder with a three-dimensional network structure, which is interspersed with active particles and conductive agents to form a mutually penetrating network structure, thereby increasing the viscosity of the binder, increasing the adhesion of the binder, and increasing the strength of the binder. This effectively alleviates the volume expansion of the silicon base, improves the performance of the battery, and improves the problem of battery capacity attenuation.

[0027] (2) In the present invention, since the binder only accounts for 1% to 10% of the weight of the active material in the battery manufacturing process, its role is often overlooked. The present invention cross-links the two binders to better maintain the integrity of the electrode structure, while allowing the active material and the conductive agent to better contact, thereby forming a good conductive network, effectively improving the rate performance and cycle life of the battery;

[0028] (3) In the present invention, the silicon negative electrode material prepared by using in-situ cross-linked P(E-alt-MA)-M and Alg composite binder has a first charge specific capacity of 1769.28 mAh / g, a coulombic efficiency of 81.83%, a reversible capacity of 1629.29 mAh / g after five cycles of activation, a capacity retention rate of 82% after 200 cycles, and a reduced capacity decay, which is much higher than that of the battery prepared using Alg alone;

[0029] (4) In the present invention, starting with the binder used in the battery manufacturing process, an alkalized polyethylene maleic acid and a natural hydroxyl-rich binder are used to prepare a composite binder, and the two binders are subjected to an in-situ condensation reaction for cross-linking to form a three-dimensional network structure. The vacuum baking temperature of the electrode is changed to maintain the integrity of the electrode structure during the electrode manufacturing process, and to make the contact between the active material and the conductive agent better, forming an excellent conductive network, thereby effectively improving the rate performance, cycle life and cycle stability of the battery, and improving the problem of capacity attenuation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a diagram of the preparation method of P(E-alt-MA)-M in Example 1;

[0031] Figure 2 This is a diagram of the action mechanism of P(E-alt-MA)-M and Alg in Example 1. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, a detailed description is given below with specific implementation methods. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] The present embodiment provides a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, including a mixed P(E-alt-MA)-0.25Li2 aqueous binder and a natural hydroxyl-rich binder, which can cross-link with each other under high temperature conditions of 150°C, effectively alleviating the silicon-based volume expansion, improving the performance of the battery, and improving the battery capacity attenuation problem.

[0035] In the prior art, since the binder only accounts for 1% to 10% of the weight of the active material in the battery manufacturing process, its role is often overlooked. Therefore, when preparing lithium battery electrode sheets, most of them only add one binder. Even if two binders are added, there is no chemical reaction between the two binders, or the conditions for the reaction cannot be reached, so the various performance of the battery cannot be further improved.

[0036] The present invention adds two kinds of binders, one is partially alkalized polyethylene maleic acid, and the other is a natural hydroxyl-rich binder. At the same time, when the electrode is baked, the vacuum baking temperature of the electrode is changed to 150°C, so that the two binders can undergo an in-situ condensation reaction, thereby cross-linking to form a composite binder with a three-dimensional network structure, interspersed with active particles and conductive agents to form an interpenetrating network structure, thereby significantly improving various aspects of the performance of the electrode and the battery.

[0037] The P(E-alt-MA)-0.25Li2 aqueous binder in the present invention is alkalized polyethylene maleic acid, including polyethylene maleic anhydride, ultrapure water and lithium hydroxide mixed with each other, wherein the weight proportion of polyethylene maleic anhydride accounts for 5% of the total weight of the P(E-alt-MA)-0.25Li2 aqueous binder.

[0038] The natural hydroxyl-rich binder in the present invention is an Alg binder or a chitosan binder or a carboxymethyl cellulose binder, and the concentration of the natural hydroxyl-rich binder is 5%. Meanwhile, the weight ratio of the P(E-alt-MA)-0.25Li2 aqueous binder to the natural hydroxyl-rich binder is 1:1.

[0039] In the prior art, in order to alleviate the volume expansion effect of carbon-coated silicon anode during the charge and discharge process, rigid polymer materials with a large number of polar groups on the side chains are generally used as binders, such as PAA, CMC, Alg, guar gum, etc. The rich polar -COOH and -OH active functional groups can form strong hydrogen bonds with active particles, but a large amount of -COOH and -OH will react with LiPF6 at high temperature to produce phosphorus fluoride, which will lead to the decomposition of carbonate solvents and affect the battery cycle.

[0040] In addition, there are also binders containing multiple functional groups prepared by copolymerization of acrylic monomers, but the reaction steps involved are relatively cumbersome. In addition, there are also some high-strength resins used as binders, such as epoxy resins, polyimides, polyaryletherketones and other thermosetting or cross-linked resins used as binders for silicon-carbon negative electrodes, but such binders generally require the use of solvents and require very high curing temperatures, making the manufacturing process of the negative electrode cumbersome and complicated, and increasing the manufacturing cost.

[0041] In the present invention, polyethylene maleic acid is first alkalized. Since the polyethylene maleic acid formed by hydrolysis of polyethylene maleic anhydride contains abundant -COOH, it has a strong hydrogen bonding effect. By introducing alkali metal ions, electrostatic repulsion can effectively stretch the polymer chain, prevent polymer aggregation, and enhance the strength of the adhesive. The preparation method of P(E-alt-MA)-M is as follows Figure 1 shown.

[0042] When lithium ions are introduced, the concentration of Li+ in the binder increases, which is more conducive to Li+ migration. When divalent metal cations are introduced, they can react with two carboxylic acids to crosslink the molecular chains, increase the viscosity of the binder, and increase the adhesion of the binder.

[0043] When preparing the silicon-based negative electrode, the P(E-alt-MA)-M binder, i.e., the P(E-alt-MA)-0.25Li2 aqueous binder prepared in this embodiment, is used in combination with the natural hydroxyl-rich binder, so that a large number of -COOH and -OH in the composite binder form a hydrogen bond dynamic network, providing a large number of bonding sites and enhancing the bonding strength; and the alkali metal ions introduced by the alkalized polyethylene maleic acid make a large number of ionic bonds in the binder, and when the silicon-based charge and discharge volume expands, the ionic bonds are more easily reversibly restored;

[0044] The most important thing is that some of the free -COOH and -OH in the binder undergo an in-situ esterification reaction during the vacuum drying of the silicon-based negative electrode, causing the linear polymer P(E-alt-MA)-M to react with the natural hydroxyl-rich binder to form a three-dimensional network structure that penetrates each other throughout the electrode. Its mechanism of action is as follows Figure 2 As shown, Figure 2 The natural hydroxyl-rich binder in the PTFE is Alg binder.

[0045] The present invention also provides a method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, which mainly comprises the following substances in the following content ratios:

[0046] Carbon-coated silicon 94%

[0047] Conductive carbon black 3%

[0048] Single-walled carbon nanotubes 1%

[0049] 5% concentration of P(E-alt-MA)-0.25Li2 aqueous binder 1%

[0050] 1% natural hydroxyl-rich binder at a concentration of 5%.

[0051] When a silicon-based negative electrode sheet is prepared using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder, the following steps are mainly included:

[0052] S1, preparation of 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder, take 2.375 parts of polyethylene maleic anhydride and 47.425 parts of ultrapure water, heat and stir to mix in a water bath, the stirring temperature is 60°C; then take 0.2 parts of lithium hydroxide and add it to the prepared polyethylene maleic anhydride solution, let it react for 4 to 6 hours until the solution is clear, and obtain a 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder;

[0053] S2, preparation of a 5% concentration natural hydroxyl-rich binder, taking 5 parts of a hydroxyl-rich compound, adding it to 95 parts of ultrapure water, heating and stirring in a water bath at a stirring temperature of 60° C., and preparing a natural hydroxyl-rich binder;

[0054] S3, preparation of negative electrode sheet, take corresponding contents of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and natural hydroxyl-rich binder, mix them in the ratio of 94:3:1:1:1, stir for 10 minutes, and obtain a uniformly dispersed slurry; take copper foil of specified size, evenly apply the prepared slurry on the surface of the copper foil, and dry it at 80°C for 10 hours, and then vacuum dry it at 150°C for 8 hours, and finally cut it into specified size to obtain a finished negative electrode sheet.

[0055] The hydroxyl-rich compound is sodium alginate powder or chitosan or sodium carboxymethyl cellulose powder.

[0056] The present invention also tests the various properties of the battery after preparing the pole piece with different composite binders prepared by different natural hydroxyl-rich binders and P(E-alt-MA)-0.25Li2 aqueous binders. In order to increase the comparison effect, the present invention also provides a comparative example, in which a single polyethylene maleic acid binder and an Alg binder are added as comparative examples. The test results are shown in Table 1. The preparation steps of each embodiment are as follows:

[0057] Embodiment 1:

[0058] S1. Preparation of 5% P(E-alt-MA)-0.25Li2 aqueous binder: Add 2.375 g of polyethylene maleic anhydride and 47.425 mL of ultrapure water into a 100 mL sample bottle, heat in a water bath at 60°C with stirring; weigh 0.2 g of lithium hydroxide, add it to the polyethylene maleic anhydride solution, and react for 4-6 hours until the mixed solution becomes clear.

[0059] S2. Preparation of 5% Alg binder: Add 5 g of sodium alginate powder and 95 g of ultrapure water into a 100 mL sample bottle, and heat in a water bath at 60°C with stirring.

[0060] S3. Mix 1.88g of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and Alg binder in the proportion of 94%, 3%, 1%, 1%, and 1%, and stir for 10 minutes to obtain a uniformly dispersed slurry. Apply the obtained slurry on copper foil, dry it with air at 80°C for 10 hours, vacuum dry it at 150°C for 2 hours, and then transfer it to 80°C for vacuum drying for 8 hours, and cut it into round electrodes with a diameter of 12mm.

[0061] Embodiment 2:

[0062] S1. Preparation of 5% P(E-alt-MA)-0.25Li2 aqueous binder: Add 2.375 g of polyethylene maleic anhydride and 47.425 mL of ultrapure water into a 100 mL sample bottle, heat in a water bath at 60°C with stirring; weigh 0.2 g of lithium hydroxide, add it to the polyethylene maleic anhydride solution, and react for 4-6 hours until the mixed solution becomes clear.

[0063] S2. Preparation of chitosan binder with a concentration of 5%: Add 5 g of chitosan powder and 95 g of ultrapure water into a 100 mL sample bottle, and heat in a water bath at 60°C with stirring.

[0064] S3. Mix 1.88g of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and chitosan binder in the proportion of 94%, 3%, 1%, 1%, and 1%, and stir for 10 minutes to obtain a uniformly dispersed slurry. Apply the obtained slurry on copper foil, dry it with air at 80°C for 10 hours, vacuum dry it at 150°C for 2 hours, and then transfer it to 80°C for vacuum drying for 8 hours, and cut it into round electrodes with a diameter of 12mm.

[0065] Embodiment 3:

[0066] S1. Preparation of 5% P(E-alt-MA)-0.25Li2 aqueous binder: Add 2.375 g of polyethylene maleic anhydride and 47.425 mL of ultrapure water into a 100 mL sample bottle, heat in a water bath at 60°C with stirring; weigh 0.2 g of lithium hydroxide, add it to the polyethylene maleic anhydride solution, and react for 4-6 hours until the mixed solution becomes clear.

[0067] S2. Preparation of 5% carboxymethyl cellulose binder: Add 5 g of sodium carboxymethyl cellulose powder and 95 g of ultrapure water into a 100 mL sample bottle, and heat in a water bath at 60°C with stirring.

[0068] S3. Mix 1.88g of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and carboxymethyl cellulose binder in the proportion of 94%, 3%, 1%, 1%, and 1%, and stir for 10 minutes to obtain a uniformly dispersed slurry. Apply the obtained slurry on copper foil, dry it with air at 80°C for 10 hours, vacuum dry it at 150°C for 2 hours, and then transfer it to 80°C for vacuum drying for 8 hours, and cut it into round electrodes with a diameter of 12mm.

[0069] Comparative Example 1 is to prepare the pole piece using polyethylene maleic acid binder alone.

[0070] Comparative Example 2 is to prepare the pole piece using Alg binder alone.

[0071] Table 1 Performance of negative electrode sheets prepared with different types of composite binders

[0072]

[0073] It can be seen from the above table that the use of this composite binder can effectively alleviate the volume expansion of silicon-based materials. The silicon negative electrode material prepared using in-situ cross-linked P(E-alt-MA)-M and Alg composite binders has the best performance, with a specific capacity of 1769.28 mAh / g at the first charge, a coulombic efficiency of 81.83%, a reversible capacity of 1629.29 mAh / g after five cycles of activation, and a capacity retention rate of 82% after 200 cycles. The capacity fluctuation and attenuation are very small, which is much higher than the battery prepared using polyethylene maleic acid binder or Alg binder alone.

[0074] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.

Claims

1. A method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermal cross-linking three-dimensional aqueous binder, characterized in that: The following steps are involved: S1, preparation of 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder, take 2.375 parts of polyethylene maleic anhydride and 47.425 parts of ultrapure water, heat and stir to mix in a water bath, the stirring temperature is 60°C; then take 0.2 parts of lithium hydroxide and add it to the prepared polyethylene maleic anhydride solution, let it react for 4 to 6 hours until the solution is clear, and obtain a 5% concentration P(E-alt-MA)-0.25Li2 aqueous binder; S2, preparation of a 5% concentration natural hydroxyl-rich binder, taking 5 parts of a hydroxyl-rich compound, adding it to 95 parts of ultrapure water, heating and stirring in a water bath at a stirring temperature of 60° C., and preparing a natural hydroxyl-rich binder; S3, preparation of negative electrode sheet, taking corresponding contents of carbon-coated silicon dioxide, conductive carbon black, single-walled carbon nanotubes, P(E-alt-MA)-0.25Li2 aqueous binder and natural hydroxyl-rich binder, mixing them in a ratio of 94:3:1:1:1, stirring for 10 minutes, and obtaining a uniformly dispersed slurry; taking copper foil of specified size, evenly coating the prepared slurry on the surface of the copper foil, and drying it with air at 80°C for 10 hours, and then vacuum drying it at 150°C for 8 hours, and finally cutting it into specified size to obtain a finished negative electrode sheet; The high-performance in-situ thermally cross-linked three-dimensional water-based binder comprises substances in the following content ratios: Carbon-coated silicon 94% Conductive carbon black 3% Single-walled carbon nanotubes 1% 5% concentration of P(E-alt-MA)-0.25Li2 aqueous binder 1% 1% natural hydroxyl-rich binder at a concentration of 5%.

2. The method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermally cross-linked three-dimensional aqueous binder according to claim 1, characterized in that: The natural hydroxyl-rich binder is made of sodium alginate, chitosan or sodium carboxymethyl cellulose.

3. The method for preparing a silicon-based negative electrode sheet using a high-performance in-situ thermal cross-linking three-dimensional aqueous binder according to claim 1, characterized in that: The hydroxyl-rich compound is sodium alginate powder or chitosan or sodium carboxymethyl cellulose powder.

Citation Information

Patent Citations

  • Silicon-based anode materials for lithium batteries and their preparation methods

    CN110380029B

  • A stable silicon-based anode material for lithium batteries and its preparation method

    CN111129479B

  • Aqueous cross-linking type binder for lithium ion battery, and preparation method and application of aqueous cross-linking type binder

    CN111697234A